Edukasi Perilaku CERDIK Sebagai Upaya Pencegahan Dini Penyakit Tidak Menular - Wiguna, I Nyoman Agus Pradnya; Diaris, Ni Made; Suputra, I Kadek Darmo; Dewi, Ni Made Umi Kartika; Apsari, Dewi Puspita; Sinarsih, Ni Ketut; Kartika, I Gusti Agung Ayu; Juniartha, Made G. (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2024)
Currently, Indonesia is not only bearing the burden of Communicable Diseases (PM) but also the burden of Non-Communicable Diseases (PTM). One of the strategies in the guidelines for non-communicable diseases management by the Prevention and Control Directorate of Non-Communicable Diseases of the Republic of Indonesia Health Ministry in 2019 is to carry out promotive, preventive, curative, rehabilitative and palliative actions as a whole , one of which is with the CERDIK principle. CERDIK behavior is a necessary behavior to prevent various kinds of non-communicable diseases. The behavior in question is regular health checks, getting rid of cigarette smoke, diligent physical activity/exercise, and a healthy and balanced diet. Therefore, Lecturers in the Yoga and Health Study Program at I Gusti Bagus Sugriwa Denpasar State Hindu University carried out community service activities by providing CERDIK behavior education with the target of activities for students at the Bali Kresna Medika Health Vocational High School (SMK). the number of participants were 32 people. The implementation method for this activity was to provide CERDIK material, yoga exercises, and physical measurements which were carried out in 5 meetings. In general, the implementation of activities ran smoothly. The success of the activity is was measured by a questionnaire. The results showed that there was an increase in participants' knowledge regarding CERDIK, namely from the category of knowledge that was quite good to very good. In the future, it is hoped that this activity can be carried out with broader targets and scope.